Local Government Unit Livelihood Program Support and Small Medium Entreprises’ Performance in Carmona, Cavite: Inputs to Socio-Economic Development Plan - John Darrel Medina; Boniebert Luciano; Clark Kim Castro (Southeast Asian Journal of Science and Technology, 2025)
Small and Medium Enterprises (SMEs) play a vital role in local economic vitality, contributing significantly to employment creation and innovation. This study evaluated the Local Government Unit (LGU) Livelihood Program Support in Carmona, Cavite, and its relationship to SME performance. Using a descriptive‑correlational design, data were gathered from 643 respondents—LGU employees, SME owners, and SME staff—via a validated researcher‑made questionnaire. Findings reveal that LGU support is generally evident, with strong results in business development services and program design. SME performance was also assessed as evident, particularly in innovation, market performance, and customer satisfaction. Statistical analyses show a moderately strong positive correlation between LGU support and SME performance, while significant differences emerged in stakeholder assessments of training, regulation, and financial support. Key problems include delays in financial assistance, limited stakeholder involvement in planning, and inconsistencies in policy implementation. Based on these findings, the study proposes evidence‑based inputs to a Socio‑Economic Development Plan (SEDP) aimed at fostering a more inclusive, efficient, and participatory SME ecosystem.